INTERNET IN CONDITIONS OF SOCIETY INFORMATIZATION - K.N. KOSHKO (Advanced Engineering Research)
In the process of the society informatization Internet has become the next technical achievemet of mankind, it is not only of informational but also of social value. “The world – wide net” is the new cultural model of the post-industrial society opening really unlimited possibilities of getting information.